Targeted sequencing and clinical strategies in children with autism spectrum disorder: A cohort study - Hu, Chunchun; Wang, Yi; Li, Chunyang; Mei, Lianni; Zhou, Bingrui; Li, Dongyun; Li, Huiping; Xu, Qiong; Xu, Xiu (Frontiers in Genetics, 2023)
Objectives: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with genetic and clinical heterogeneity. Owing to the advancement of sequencing technologies, an increasing number of ASD-related genes have been reported. We designed a targeted sequencing panel (TSP) for ASD based on next-generation sequencing (NGS) to provide clinical strategies for genetic testing of ASD and its subgroups. Methods: TSP comprised 568 ASD-related genes and analyzed both single nucleotide variations (SNVs) and copy number variations (CNVs). The Autism Diagnostic Observation Schedule (ADOS) and the Griffiths Mental Development Scales (GMDS) were performed with the consent of ASD parents. Additional medical information of the selected cases was recorded. Results: A total of 160 ASD children were enrolled in the cohort (male to female ratio 3.6:1). The total diagnostic yield was 51.3% for TSP (82/160), among which SNVs and CNVs accounted for 45.6% (73/160) and 8.1% (13/160), respectively, with 4 children having both SNVs and CNV variants (2.5%). The detection rate of disease-causing variants in females (71.4%) was significantly higher than that in males (45.6%, P=0.007). SHANK3, KMT2A, and DLGAP2 were the most frequent variants among these patients. Eleven children had de novo SNVs, 2 of whom had de novo ASXL3 variants with mild global developmental delay (DD) and minor dysmorphic facial features besides autistic symptoms. Seventy-one children completed both ADOS and GMDS, of whom 51 had DD/intellectual disability (ID). In this subgroup of ASD children with DD/ID, we found that children with genetic abnormalities had lower language competence than those without positive genetic findings (P=0.028). There was no correlation between the severity of ASD and positive genetic findings. Conclusion: Our study revealed the potential of TSP, with lower cost and more efficient genetic diagnosis. We recommended that ASD children with DD or ID, especially those with lower language competence, undergo genetic testing. More precise clinical phenotypes may help in the decision-making of patients with genetic testing.